2000
DOI: 10.1042/bj3500589
|View full text |Cite
|
Sign up to set email alerts
|

Fetuin-B, a second member of the fetuin family in mammals

Abstract: A set of orthologous plasma proteins found in human, sheep, pig, cow and rodents, now collectively designated fetuin-A, constitutes the fetuin family. Fetuin-A has been identified as a major protein during fetal life and is also involved in important functions such as inhibition of the insulin receptor tyrosine kinase activity, protease inhibitory activities and development-associated regulation of calcium metabolism and osteogenesis. Furthermore, fetuin-A is a key partner in the recovery phase of an acute inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(31 citation statements)
references
References 47 publications
(114 reference statements)
1
28
0
Order By: Relevance
“…For this reason, many biomarkers have been identified to predict risk of cardiovascular events in women with PCOS [22,23]. CIMT is a good indicator of cardiovascular risk and is strongly associated with conventional cardiovascular risk factors [5,6]. In the present study, we found that CIMT was increased in PCOS subjects compared to controls.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…For this reason, many biomarkers have been identified to predict risk of cardiovascular events in women with PCOS [22,23]. CIMT is a good indicator of cardiovascular risk and is strongly associated with conventional cardiovascular risk factors [5,6]. In the present study, we found that CIMT was increased in PCOS subjects compared to controls.…”
Section: Discussionsupporting
confidence: 55%
“…Fetuin-B is a novel pluripotent peptide hormone which is a member of the cystatin super family of cysteine protease [5]. It is secreted from various tissues such as liver and adipose tissue [6]. Growing evidence suggest that fetuin-B plays a crucial role in glucose metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Fetuin-B is a member of the fetuin family, part of the cystatin superfamily of cysteine protease inhibitors (7) and is predominantly expressed in the liver (8, 9), but also, to a lesser extent, in other tissues, such as placenta (10), white adipose tissue and heart (8). It has been shown that fetuin-B could be activated by agonists of farnesoid X receptor, which is a key factor in the regulation of lipid and carbohydrate metabolism (11).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to impaired insulin secretion from pancreatic cells, a reduced insulin sensitivity is found to play a predominant role in the pathogenesis of the disease (2). Several circulating proteins are involved in the regulation of insulin sensitivity; such as, adiponectin, retinol binding protein 4, and fetuin-A (3). The fetuin family consists of a set of orthologous plasma proteins found in humans, sheep, pigs, cows and rodents.…”
Section: Dear Editormentioning
confidence: 99%
“…Fetuin-B was discovered in mice prone to diabetes. Based on domain homology, overall conservation of cysteine residues and chromosomal assignments of the corresponding genes in these species, fetuin-B is a unambiguously paralogue of fetuin-A (3, 4). Recently, fetuin-B has also been identified as a novel adipokine/hepatokine which is significantly increased in hepatic steatosis and which mediates impaired insulin action, as well as glucose intolerance (4).…”
Section: Dear Editormentioning
confidence: 99%